Analisis Pengaruh Kompetisi, Capital Buffer, Inklusi Keuangan, dan Ukuran Bank terhadap Stabilitas Perbankan di Indonesia - Gumanica, Meginta (Contemporary Studies in Economic, Finance and Banking, 2022)
Apart from being an intermediary institution in the economy, banks also play a role in carrying out the transmission function. Therefore, a stable banking system is needed to stimulate the economy and maintain financial system stability to anticipate financial crises. This study investigates the effects of competition, capital buffer, financial inclusion, and bank size on Indonesia's banking system's stability between 2015-2020. This study uses the panel data regression method. The results show that the banking sector supports the competition-fragility hypothesis, which means that a low level of competition can increase bank stability. This study finds that capital buffer and bank size positively impact bank stability. However, financial inclusion only has a positive impact on the stability of large banks but has a negative impact on small banks. It is said that financial inclusion will increase stability in banks with better supervision. In addition, this study finds that larger banks have higher market power and stability than small banks. Therefore, the result supports the implementation of POJK Konsolidasi Bank Umum in improving banking stability through increasing the quantity of bank capital.